An Explorative Study on Educational Knowledge Management in Supply and Chain - Mohd Yaakob, Mohd Faiz; Yusof, Mat Rahimi; Habibi, Akhmad; Mukminin, Amirul; Setambah, Mohd Afifi Baharuddin (ExcelingTech, 2019)
Realizing the importance of knowledge management (KM) in improving the supply chain; KM is identified as one of the sustainable factors to educational achievement. The purpose of this study was to explore the knowledge management among principals and teachers in high performance schools in Malaysia. Information was gathered from six teachers and four principals from four different schools in Northern Malaysia. The data was collected through demographic profiles and semi-structured interviews. We identified five major themes related to teachers and principals in managing knowledge management in school; (1) Knowledge Received, (2) Knowledge Documentation, (3) Knowledge Sharing, (4) Knowledge Creation, and (5) Knowledge Application. Policy implications and suggestions for future research are also discussed.